If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (Z + 2)(9x + -5) = 0 Reorder the terms: (2 + Z)(9x + -5) = 0 Reorder the terms: (2 + Z)(-5 + 9x) = 0 Multiply (2 + Z) * (-5 + 9x) (2(-5 + 9x) + Z(-5 + 9x)) = 0 ((-5 * 2 + 9x * 2) + Z(-5 + 9x)) = 0 ((-10 + 18x) + Z(-5 + 9x)) = 0 (-10 + 18x + (-5 * Z + 9x * Z)) = 0 (-10 + 18x + (-5Z + 9xZ)) = 0 Reorder the terms: (-10 + -5Z + 18x + 9xZ) = 0 (-10 + -5Z + 18x + 9xZ) = 0 Solving -10 + -5Z + 18x + 9xZ = 0 Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '10' to each side of the equation. -10 + -5Z + 18x + 10 + 9xZ = 0 + 10 Reorder the terms: -10 + 10 + -5Z + 18x + 9xZ = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -5Z + 18x + 9xZ = 0 + 10 -5Z + 18x + 9xZ = 0 + 10 Combine like terms: 0 + 10 = 10 -5Z + 18x + 9xZ = 10 Add '-18x' to each side of the equation. -5Z + 18x + -18x + 9xZ = 10 + -18x Combine like terms: 18x + -18x = 0 -5Z + 0 + 9xZ = 10 + -18x -5Z + 9xZ = 10 + -18x Reorder the terms: -10 + -5Z + 18x + 9xZ = 10 + -18x + -10 + 18x Reorder the terms: -10 + -5Z + 18x + 9xZ = 10 + -10 + -18x + 18x Combine like terms: 10 + -10 = 0 -10 + -5Z + 18x + 9xZ = 0 + -18x + 18x -10 + -5Z + 18x + 9xZ = -18x + 18x Combine like terms: -18x + 18x = 0 -10 + -5Z + 18x + 9xZ = 0 The solution to this equation could not be determined.
| 12x+y=-3 | | 2b^2+5b-63=0 | | 261=79-x | | 1/x-1/x+1=1/x(2)+x | | 27-6z=-5(7z-9) | | X*2X=166 | | -16=4y-9 | | 2(8b+2)-1+4g-(2-5g)= | | -x-7=x+1 | | x=160-(170-x) | | 43=3u-11 | | x^3-12x^2-6x-12=0 | | 33b-23=b | | 29-5x=9-7x | | 12A-7=-1 | | y=0.15x+0.15 | | 7-4a=2a+2-5a | | 12=6-2y | | y-1=1/5(x-3) | | solvingx^3-12x^2-6x-12=0 | | -7-x=1+x | | -(7-7a)+4a=-23+3a | | 20x^2(-3+4x)=0 | | 1/3x-5/6x=17 | | 157=11-w | | 21x+42=-3 | | 2b^2+5b-62=0 | | 4x-11=3x+3 | | 7-g=-11 | | Y=5/2-20 | | 17j-13j=16 | | 6x+8y=480 |